2021
DOI: 10.3390/rs13010155
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Deep Machine Learning for the Automated Selection of Remote Sensing Data for the Determination of Areas of Arable Land Degradation Processes Distribution

Abstract: Soil degradation processes are widespread on agricultural land. Ground-based methods for detecting degradation require a lot of labor and time. Remote methods based on the analysis of vegetation indices can significantly reduce the volume of ground surveys. Currently, machine learning methods are increasingly being used to analyze remote sensing data. In this paper, the task is set to apply deep machine learning methods and methods of vegetation indices calculation to automate the detection of areas of soil de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 68 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…In this paper, we have systematically reviewed the stateof-art machine learning and deep learning techniques in remote sensing data analysis [67]. The deep learning techniques were originally rooted in machine learning fields for classification and recognition tasks, and they have only recently appeared in the remote sensing and geoscience community [30].…”
Section: Sn Computer Sciencementioning
confidence: 99%
“…In this paper, we have systematically reviewed the stateof-art machine learning and deep learning techniques in remote sensing data analysis [67]. The deep learning techniques were originally rooted in machine learning fields for classification and recognition tasks, and they have only recently appeared in the remote sensing and geoscience community [30].…”
Section: Sn Computer Sciencementioning
confidence: 99%
“…The tool's capacity to forecast future LD is based on machine learning (ML) models for forecasting future LD/SDS. The applications of ML to forecast LD (Grinand et al, 2020; Rukhovich et al, 2021; Torabi et al, 2021), as well as SDS (Boroughani et al, 2020; Jiao et al, 2021), have been recently demonstrated. We evaluated the ML‐LDT prototype over two study areas in the Indian Thar Desert and Inner Mongolia, China.…”
Section: Introductionmentioning
confidence: 99%
“…For such scales, the instruction on soil mapping of 1973 applies to the territory of Russia [1]. Often, instead of soil cover mapping, various methods of indicative botany were used in the form of analyses of vegetation indices [2][3][4][5][6][7]. An alternative to vegetation indices is the method of constructing soil maps based on the analysis of the bare soil surface [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Clouds masks are in open access [43]. The disadvantages of existing cloud masks require new filtering methods based on deep machine learning and computer vision [6,[44][45][46][47]. It can be assumed that the use of deep machine learning will make it possible to select the necessary satellite images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation